1988
DOI: 10.1002/aic.690341022
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical extraction of crotalaria spectabilis in the cross‐over region

Abstract: Chimowitz and Pennisi (1986) have recently described a novel process for the separation and purification of components from mixtures of solutes in supercritical fluids. Their process was based on operation in the multicomponent temperaturesolubility cross-over region. For a single solute, the cross-over point (~3 y / a T )~ = 0 represents the pressure a t which there is a change in the temperature dependence of the solubility. Below this pressure, solubility is principally dependent on solvent density and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Separation of isomers using retrograde crystallization therefore seems unlikely, although Johnston et al (1987) have identified one candidate system (2,3-and 2,6-dimethylnaphthalene). The technical feasibility of retrograde crystallization has been demonstrated in other nonisomeric systems with varying degrees of success (Kelley and Chimowitz, 1989;Schaeffer et al, 1988). In practice, crossover regions tend to be quite narrow, perhaps less than 20 bar, and are difficult to define because a distinct crossover pressure does not necessarily exist for all temperatures between two isotherms (see Figure 3).…”
Section: Separation Of Para Ortho Isomersmentioning
confidence: 99%
“…Separation of isomers using retrograde crystallization therefore seems unlikely, although Johnston et al (1987) have identified one candidate system (2,3-and 2,6-dimethylnaphthalene). The technical feasibility of retrograde crystallization has been demonstrated in other nonisomeric systems with varying degrees of success (Kelley and Chimowitz, 1989;Schaeffer et al, 1988). In practice, crossover regions tend to be quite narrow, perhaps less than 20 bar, and are difficult to define because a distinct crossover pressure does not necessarily exist for all temperatures between two isotherms (see Figure 3).…”
Section: Separation Of Para Ortho Isomersmentioning
confidence: 99%
“…Hence, the values of Kp were nearly constant and varied from 3 to 3.3 as shown also in Figure 4. The pressure at which the effect of temperature on solubility reverses has been termed the crossover point (Chimowitz and Pennisi, 1986;Schaeffer et al 1988). Our results for Kp indicate that a similar crossover pressure exists for desorption and that for ethyl acetate desorbing from activated carbon into C02 this pressure is near 13 MPa.…”
Section: Eflect Of Temperaturementioning
confidence: 99%
“…An increase in the cross over pressure is normally detected in solubility isotherms obtained using supercritical solvents modified with a co-solvent due to the increase in the critical temperature and pressure of the mixed solvent. 26 These authors observed that varying the concentration of ethanol in supercritical CO 2 from 0 to 10% resulted in an increase in the crossover pressure of monocrotaline solubility isotherms from 7.5 to 27.5 MPa.…”
mentioning
confidence: 98%